Ensino remoto na educação superior: evidências da manifestação da afetividade - Oliveira, Fabiana Aparecida de (2021)
The following dissertation is inserted in the research field of New Technologies at the post graduation program in Education: Curriculum from the Pontifícia Universidade Católica of São Paulo. The study reflects the evidence of affectivity that has emerged and marked the learning and the e-learning process in 2020, due to the pandemic, highlighted in the teachers-students relationship. The study is founded in a concept of affectivity by Henri Wallon. This exposition has a qualitative approach and displays a systematic review of scientific production texts (thesis, dissertations, and articles) that concern affectivity in the virtual learning environment related themes. The research identifies that the evidence of affection in the academy environment, during remote and online classes, is present and interferes in the motivational aspects and cognitive process, also in the learning involvement and in teacher-student relationships